2015
DOI: 10.5455/msm.2015.27.333-336
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Caregiver Burden in Caregivers of Hemodialysis Patients

Abstract: Background:Chronic renal failure is among the chronic disease which due to persistence of the disease and long treatment process has various effects on the physiological, psychological, functional ability, lifestyle changes, and independence status of the patient and his family. This may result in the burden feeling in caregivers. According to the importance of the subject, this study is to assess the level of caregiver burden in caregivers of hemodialysis patients.Methods:This is a cross-sectional analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 9 publications
14
107
3
7
Order By: Relevance
“…Caregiver burden, by definition, refers to a high level of stress that may be experienced by people who are caring for another person (usually a family member) with some kind of illness. For example, a person caring for someone with a chronic illness may experience such stressors as financial strain, managing the person's symptoms, dealing with crises, the loss of friends, or the loss of intimacy (Mashayekhi et al, 2015). In our knowledge, there was no available information on social support and caregiver's burden among parents of β-thalassemia major children.…”
Section: Introductionmentioning
confidence: 78%
“…Caregiver burden, by definition, refers to a high level of stress that may be experienced by people who are caring for another person (usually a family member) with some kind of illness. For example, a person caring for someone with a chronic illness may experience such stressors as financial strain, managing the person's symptoms, dealing with crises, the loss of friends, or the loss of intimacy (Mashayekhi et al, 2015). In our knowledge, there was no available information on social support and caregiver's burden among parents of β-thalassemia major children.…”
Section: Introductionmentioning
confidence: 78%
“…Patients diagnosed with end‐stage renal disease (ESRD) visit haemodialysis facilities for the remainder of their lives unless they undergo a kidney transplant; family carers frequently accompany the patient for treatment 3 days a week and on each occasion spend 3–4 hr in a waiting area. The patients and family carers undergo considerably higher stress and have less flexibility in family adaptability than healthy individuals and their families (Jiang et al., ; Mashayekhi, Pilevarzadeh, & Rafati, ; Pereira et al., ). Particularly strong family ties characterize Korean culture; hence, dependency on family members in times of illness is high.…”
Section: Introductionmentioning
confidence: 99%
“…Mashayekhi et al [14] found that 72.5% of the caregivers had average to severe burden. Caregivers who had low quality of life had high rates of burden and high scores of depression [11].…”
Section: Caregivers' Burdenmentioning
confidence: 99%
“…Caregivers are involved in patients' care and assistance during haemodialysis in order to help them adapt and efectively manage their treatment [14]. They help patients with their daily activities, household tasks, and personal care, such as bathing and dressing, while they undertake responsibility for technical health procedures in dialysis [15].…”
Section: Caregivers' Role In Haemodialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation